2016
DOI: 10.1164/rccm.201512-2393oc
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Reliability of Internet Resources for Information on Idiopathic Pulmonary Fibrosis

Abstract: Patient-directed online information on IPF is frequently incomplete, inaccurate, and outdated. There is no reliable method for patients to identify sites that provide appropriate information on IPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 14 publications
5
109
1
Order By: Relevance
“…In a study of postpartum depression, for example, much of the information on websites about this condition was inaccurate or incomplete and pitched at a high level of readability (Moore & Ayers, ; Summers & Logsdon, ). Similar findings have been reported in analyses of websites for conditions as diverse as oral leukoplakia (Wiriyakijja, Fedele, Porter, & Riordain, ), pulmonary fibrosis (Fisher, O'Connor, Flexman, Shapera, & Ryerson, ) and pancreatic cancer (Storino et al., ). Much less visible are website analyses of health problems that frequently fall into the nursing domain, such as managing symptoms of fatigue.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…In a study of postpartum depression, for example, much of the information on websites about this condition was inaccurate or incomplete and pitched at a high level of readability (Moore & Ayers, ; Summers & Logsdon, ). Similar findings have been reported in analyses of websites for conditions as diverse as oral leukoplakia (Wiriyakijja, Fedele, Porter, & Riordain, ), pulmonary fibrosis (Fisher, O'Connor, Flexman, Shapera, & Ryerson, ) and pancreatic cancer (Storino et al., ). Much less visible are website analyses of health problems that frequently fall into the nursing domain, such as managing symptoms of fatigue.…”
Section: Introductionsupporting
confidence: 79%
“…Exemplary published studies evaluating consumer‐oriented websites also are a source for identifying methods of reviewing websites on health topics (e.g. Fisher et al., ; Moore & Ayers, ; Storino et al., ; Wiriyakijja et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the patients surveyed searched for more information on IPF online; however, a recently published analysis found that online health information on IPF is frequently incomplete, inaccurate, and outdated [32]. Results from other surveys suggest that the majority of patients want to be provided with more information about IPF, including its progression and treatment [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Participants' RA knowledge scores were on average only moderate, a finding that supports their desire for more information 7 . Now a days, Increasingly, patients are turning to internet, websites and chat rooms for advice, and some of these may be of poor quality 7 . Rheumatology nurses have an important role in educating patients with rheumatoid arthritis.…”
mentioning
confidence: 79%